2020
DOI: 10.5194/tc-2020-147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grounding zone subglacial properties from calibrated active source seismic methods

Abstract: Abstract. The grounding zone of Whillans Ice Stream, West Antarctica, exhibits an abrupt transition in basal properties from the grounded ice to the ocean cavity over distances of less than 0.5–1 km. Active source seismic methods reveal the grounded portion of the ice stream is underlain by a relatively stiff substrate (relatively high shear wave velocities) compared to the deformable till found elsewhere beneath the ice stream. Several kilometers upstream of the grounding zone, layers of subglacial water are … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Horgan et al (2021) found relatively stiff till at the grounding line of Whillans Ice Stream compared to the main ice trunk. The stiffer till at the grounding line creates more basal drag and consequently a slowdown of ice, leading to a thickening of ice, which stabilizes the position of the grounding line (Joughin et al, 2005;Anandakrishnan et al, 2007;Horgan et al, 2021). A softening of the till at the grounding line through basal friction changes would change the position of the grounding line and discharge rates.…”
Section: Sensitivity To Changes In Basal Friction and Ice Rigiditymentioning
confidence: 90%
“…Horgan et al (2021) found relatively stiff till at the grounding line of Whillans Ice Stream compared to the main ice trunk. The stiffer till at the grounding line creates more basal drag and consequently a slowdown of ice, leading to a thickening of ice, which stabilizes the position of the grounding line (Joughin et al, 2005;Anandakrishnan et al, 2007;Horgan et al, 2021). A softening of the till at the grounding line through basal friction changes would change the position of the grounding line and discharge rates.…”
Section: Sensitivity To Changes In Basal Friction and Ice Rigiditymentioning
confidence: 90%
“…Basal properties derived from seismic datasets and numerical models also provide evidence for strong, cohesive sediments at Antarctic grounding zones that could be extruded to form, and preserve, the corrugation ridges. At the best studied Antarctic example, Whillans Ice Stream, seismic properties (ρ, Vp, Vs) indicate significant stiffening of a 5-m till layer over a sharp transition at its grounding zone, when compared with upstream sites (Horgan et al, 2021). This stiff, low permeability substrate at the grounding zone is consistent with models of ice-shelf flexure (for fixed and tidally migrating grounding lines) that predict compression, and potentially dewatering of subglacial till, immediately upstream the grounding zone as ice bends down into the substrate at high tide (Walker et al, 2013;Sayag and Worster, 2013).…”
Section: Till Extrusion Mechanismmentioning
confidence: 99%
“…As pointed out by Graham et al (2022), the strong tidal periodicity of the corrugation ridge dimensions should, therefore, indicate a high permeability substrate in the region of ridge formation despite observational evidence that most subglacial tills are cohesive and likely to have low permeabilities. They addressed this problem by suggesting that water may drain out of the grounding zone via a series of shallow canals, although another alternative is that the pattern of groundingline migration at Thwaites is not controlled by fluid connectivity through the till, as has been suggested for the Whillans grounding zone (Horgan et al, 2021).…”
Section: Till Extrusion Mechanismmentioning
confidence: 99%